Small supernumerary marker chromosomes derived from human chromosome 11 - Liehr, Thomas; Ziegler, Monika; Person, Luisa; Kankel, Stefanie; Padutsch, Niklas; Weise, Anja; Weimer, Jörg Paul; Williams, Heather; Ferreira, Susana; Melo, Joana B.; Carreira, Isabel M. (Frontiers in Genetics, 2023)
With only 39 reported cases in the literature, carriers of a small supernumerary marker chromosome (sSMC) derived from chromosome 11 represent an extremely rare cytogenomic condition. Herein, we present a review of reported sSMC(11), add 18 previously unpublished cases, and closely review eight cases classified as 'centromere-near partial trisomy 11' and further four suited cases from DECIPHER. Based on these data, we deduced the borders of the pericentric regions associated with clinical symptoms into a range of 2.63 and 0.96 Mb for chromosome 11 short (p) and long (q) arms, respectively. In addition, the minimal pericentric region of chromosome 11 without triplo-sensitive genes was narrowed to positions 47.68 and 60.52 Mb (GRCh37). Furthermore, there are apparent differences in the presentation of signs and symptoms in carriers of larger sSMCs derived from chromosome 11, when the partial trisomy is derived from different chromosome arms. However, the number of informative sSMC(11) cases remains scarce, with overlapping presentation between pand q-arm-imbalances. In addition, uniparental disomy (UPD) of 'normal' chromosomes 11 need to be considered in the evaluation of sSMC(11) carriers, as imprinting may be an influencing factor, although no such cases have been reported. Comprehensively, prenatal sSMC(11) cases remain a diagnostic and prognostic challenge.